2014
DOI: 10.1212/wnl.0000000000001070
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sporadic inclusion body myositis with bimagrumab

Abstract: Objective: To study activin signaling and its blockade in sporadic inclusion body myositis (sIBM) through translational studies and a randomized controlled trial. Methods:We measured transforming growth factor b signaling by SMAD2/3 phosphorylation in muscle biopsies of 50 patients with neuromuscular disease (17 with sIBM). We tested inhibition of activin receptors IIA and IIB (ActRII) in 14 patients with sIBM using one dose of bimagrumab (n 5 11) or placebo (n 5 3). The primary outcome was the change in ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 24 publications
4
146
1
5
Order By: Relevance
“…To date, bimagrumab, a selective anti-type II activin receptor monoclonal antibody preventing myostatin activity, has shown to be effective in humans with inclusion body myositis 28 , possibly becoming in the near future a therapeutic option to prevent muscular modifications in SCI and other pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To date, bimagrumab, a selective anti-type II activin receptor monoclonal antibody preventing myostatin activity, has shown to be effective in humans with inclusion body myositis 28 , possibly becoming in the near future a therapeutic option to prevent muscular modifications in SCI and other pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…77 Trials targeting muscle-inhibiting TGF-β molecules or muscle growth factors are in progress. Bimagrumab, an antibody that inhibits the signaling of a TGF-β superfamily receptor, was shown in a small-scale study to increase muscle volume after 8 weeks, 78 which has prompted an ongoing controlled study (ClinicalTrials.gov number, NCT01925209). A small, controlled, proof-ofconcept study of arimoclomol (ClinicalTrials.gov number, NCT00769860), an agent that up-regulates heat shock protein response and attenuates cell stress, has been completed; the drug had an acceptable adverse-event profile, but whether there were clinically meaningful benefits is still unclear.…”
Section: Tr E Atment Of Der M At Om Yositis Polym Yositis a Nd Necrmentioning
confidence: 99%
“…These include a current multi-centre international phase 2b/3 doubleblinded placebo-controlled randomised controlled trial of bimagrumab (clinical trials identifier NCT01925209), which is a fully humanized monoclonal antibody that blocks the activin IIA and IIB receptors that bind myostatin and other ligands, thereby allowing uninhibited muscle growth and promoting muscle hypertrophy. This approach appears to be promising as a previous phase IIa trial in 14 IBM patients demonstrated an increase in thigh muscle volume and improved performance with the 6-minute walk test after a single infusion of bimagrumab (Amato et al, 2014). A gene therapy approach using follistatin to inhibit myostatin expression is also being tested using an adeno-associated virus vector and direct intramuscular injection into the quadriceps muscle (clinical trials identifier NCT01519349) .…”
Section: Treatmentmentioning
confidence: 99%
“…There has also been further recognition of racial and ethnic differences in the prevalence of the disease and of the importance of genetic factors in determining disease susceptibility. In addition, there have been advances in the search for disease biomarkers, such as the identification of the anti-cNA1 antibody (Larman et al, 2013, Pluk et al, 2013 and in the application of muscle imaging techniques such as MRI and ultrasound as tools for diagnosis and monitoring outcomes in trials of new therapies (Amato et al, 2014).…”
Section: Introductionmentioning
confidence: 99%